Parental divorce and trust - Viitanen, Tarja (My University, 2011)
This paper examines the effect of parental divorce during childhood on generalised trust later on in life using Australian HILDA panel data for 2005-6. The dependent variable is composed from variations in agreement with the statement: “Generally speaking, most people can be trusted”. The main explanatory variables include the occurrence of parental divorce for the whole sample of 15-29 year olds and the age at which parents divorced for the sub-sample. The analysis is conducted using pooled OLS, pooled ordered probit, and an instrumental variables regression to account for possible endogeneity issues. The results are not significant for men for whom parental divorce does not have a significant effect on their expressed level of generalised trust. However, the results for women indicate that their level of generalised trust is significantly affected by parental divorce with women who have experienced parental divorce expressing lower levels of generalised trust.
Keywords: Relationships; Relationships -- Divorce; Beliefs and Values; Beliefs and Values -- Personality; Identity; Relationships; Beliefs and Values; Divorce; Personality; Identity